Application of rubber coated textiles in personal protective equipement and medical devices - Banerjee Bireswar (Rubber India, 2013)
The most significant and important technology for implementation of Rubber coated textiles in the construction of personal protective, therapeautic and life saving equipments. These devices are useful to the common men to Defence contrivance in the instrumentatio of para - military, Military, Naval forces and in Air force combating operations. Some of the devices are designed & prepared from rubberised fabric equipped in the treatement of serious chronic diseases such as low back pain inflatable bed, water bed for bed sore patients, in the management of ailments like filariasis and concerning to monitor sleeping disoders etc. A few of such items made from cotton / man-made textiles coated with natural rubber / natural rubber & blend of general purpose synthetic rubbers / special purpose synthetic rubber composition have been expounded in this article.
Keywords: Anti Gravity Suit; Apnea; CBRN; Lymphoedema; Military Ponchos